anonymous
  • anonymous
Evaluate f(x) = x 2 + 1 for f(-1). a.0 b.undefined c.2
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
SnuggieLad
  • SnuggieLad
Do this the same way you did it before. X=1...put -1 in for x in that problem
SnuggieLad
  • SnuggieLad
(-1)*2+1
SnuggieLad
  • SnuggieLad
or also written it is 2(-1) + 1

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

Hero
  • Hero
f(x) = x^2 + 1 f(-1)= (-1)^2 + 1 = 1 + 1 = ?
SnuggieLad
  • SnuggieLad
Hold on? Is that a square root? Be sure to write that out next time
SnuggieLad
  • SnuggieLad
Well done @Hero
Hero
  • Hero
Its \(f(x) = x^2 + 1\) Sometimes when students copy and paste, they forget to add the caret.
anonymous
  • anonymous
ok so the answer is 2 thanks a lot
SnuggieLad
  • SnuggieLad
Yes, I should have picked up on that.
anonymous
  • anonymous
can you guys help me with one more its Evaluate f(x) = x^ 2 + 1 for f(10). a.2√2 b.101 c.21
Hero
  • Hero
f(x) = x^2 + 1 f(10) = (10)^2 + 1 = 100 + 1 = ?
anonymous
  • anonymous
what about this one? If f(x) = x 2 + 1 and g(x) = 3x + 1, find [f(2)-g(1)] 2. a.1 b.2 c.9
Hero
  • Hero
I thought you said you only had one more....You tricked me :)
anonymous
  • anonymous
sorry...lol this is the last one.
Hero
  • Hero
f(2) - g(1) = (2)^2 + 1 -(3(1) + 1) = 4 + 1 - 3 - 1 = 5 - 4 = ?
anonymous
  • anonymous
thanks

Looking for something else?

Not the answer you are looking for? Search for more explanations.